Learning Theories And Their Implications in Islamic Education - Misbakhul Amri; Raden Bagus Aribowo; Ipran Syah; Relawati; Mir'atul Ngulya; Siti Roudhotul Jannah (JOSAR (Journal of Students Academic Research), 2026)
This study examines learning theories and their implications in Islamic education, aiming to explore how concepts of modern learning theories can be integrated with Islamic values in the learning process. The learning theories discussed include behaviorism, cognitivism, constructivism, humanism, and Qur’anic learning theory, which encompasses tadabbur, tafakkur, and ta’lim. This research employs a qualitative approach using library research methods, drawing on books, scholarly journals, and relevant literature related to learning theories and Islamic education. Data were collected through documentation study, while data analysis was conducted using content analysis techniques by classifying, interpreting, and drawing conclusions based on the research themes.The findings indicate that each learning theory contributes significantly to Islamic education. Behaviorism plays a role in habit formation through reinforcement and repetition; cognitivism emphasizes critical thinking processes in understanding Islamic teachings; constructivism highlights active, experience-based learning; and humanism focuses on the development of learners’ potential and humanistic aspects. Qur’anic learning theory strengthens the spiritual dimension through tadabbur, tafakkur, and ta’lim, emphasizing a balance between knowledge, faith, and morals.The implications of learning theories in Islamic education suggest the need for learning strategies that are more active, interactive, and learner-centered while integrating Islamic values. Although challenges exist in unifying modern theoretical paradigms with Islamic principles, there are significant opportunities to develop more innovative and relevant learning models in response to contemporary developments.